Packaging structure, manufacturing method of packaging structure, and solid-state battery

CN122968537APending Publication Date: 2026-10-23ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611453185.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]然而,在一些场景下,聚丙烯层会发生软化、溶胀,并析出小分子有机物,进而污染固态电解质界面,导致电芯的电化学性能及循环寿命降低

Benefits of technology

[0038]本申请实施例提供的封装结构、封装结构的制作方法及固态电池,该封装结构的内衬复合层采用包含聚醚醚酮的材料,聚醚醚酮具有优异的耐热稳定性,在固态电池的高温工作区间及热压封装工况下分子链段保持稳定,不会发生软化溶胀与小分子有机物析出,从而有效避免了固态电解质界面受到污染。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968537A_ABST
    Figure CN122968537A_ABST
Patent Text Reader

Abstract

The embodiment of the application provides a packaging structure, a manufacturing method of the packaging structure and a solid-state battery, and relates to the technical field of batteries. The packaging structure comprises a protective layer, a metal barrier layer and an inner lining composite layer which are sequentially stacked. The inner lining composite layer comprises polyether ether ketone, and the inner lining composite layer is used for contacting a solid-state battery core. The metal barrier layer has a plurality of spaced-arranged embedded holes on one side of the metal barrier layer facing the inner lining composite layer, and part of the inner lining composite layer is embedded into the embedded holes. The packaging structure of the embodiment of the application can prevent the inner lining composite layer from precipitating small-molecule organic substances, so that the solid-state electrolyte interface is not polluted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a packaging structure, a method for manufacturing the packaging structure, and a solid-state battery. Background Technology

[0002] With the rapid development of the new energy industry, solid-state batteries have become an important development direction for next-generation power batteries due to their higher safety and energy density. Solid-state batteries also require sealing of the solid-state cells through encapsulation structures to isolate them from external moisture and oxygen corrosion of the internal materials. Therefore, the performance of the solid-state cell encapsulation structure directly affects the lifespan and safety of the all-solid-state battery.

[0003] Related technologies provide an aluminum-plastic film used as an encapsulation structure for battery cells. Specifically, the aluminum-plastic film includes a nylon layer, an aluminum foil layer, and a polypropylene layer stacked sequentially from the outside to the inside. The nylon layer is located on the outermost side, providing protection against external mechanical scratches and abrasion. The aluminum foil layer is located in the middle layer, preventing the penetration of moisture and oxygen. The polypropylene layer is located on the innermost side and is bonded to the polypropylene layer of another aluminum-plastic film by heat fusion bonding to form a sealed cavity, thereby achieving sealed encapsulation of the battery cell.

[0004] However, in some scenarios, the polypropylene layer may soften, swell, and release small molecule organic matter, which in turn contaminates the solid electrolyte interface, leading to a reduction in the electrochemical performance and cycle life of the battery cell. Summary of the Invention

[0005] This application provides a packaging structure, a method for manufacturing the packaging structure, and a solid-state battery. The inner liner composite layer will not precipitate small molecule organic matter, thus avoiding contamination of the solid electrolyte interface.

[0006] In a first aspect, embodiments of this application provide a packaging structure for packaging a solid-state battery cell, comprising a protective layer, a metal barrier layer, and an inner liner composite layer stacked sequentially. The inner liner composite layer comprises polyetheretherketone (PEEK) and is used to contact the solid-state battery cell. The side of the metal barrier layer facing the inner liner composite layer has a plurality of spaced-apart fitting holes, and a portion of the inner liner composite layer is embedded within these fitting holes.

[0007] In some possible implementations, the interlocking holes are anodic oxide holes.

[0008] And / or, the depth of the fitting hole along the stacking direction of the packaging structure is 5μm~25μm.

[0009] And / or, the protective layer is a nylon layer.

[0010] And / or, the metal barrier layer is an aluminum foil layer.

[0011] And / or, the thickness of the protective layer along the stacking direction of the encapsulation structure is 15μm~35μm.

[0012] And / or, the thickness of the metal barrier layer along the stacking direction of the packaging structure is 30μm~50μm.

[0013] In some possible implementations, the liner composite layer includes an adhesive layer and a liner layer stacked together, the adhesive layer being disposed between the metal barrier layer and the liner layer, and at least a portion of the adhesive layer being embedded in a pore, the liner layer comprising polyetheretherketone.

[0014] Alternatively, the inner liner composite layer includes an inner liner layer comprising polyetheretherketone, with a portion of the inner liner layer embedded within interlocking pores.

[0015] In some possible implementations, the liner is composed of polyetheretherketone (PEEK), or the liner comprises PEEK and reinforcing fibers.

[0016] And / or, the thickness of the inner liner layer along the stacking direction of the encapsulation structure is 30μm~80μm.

[0017] And / or, the adhesive layer is a polyetherimide layer.

[0018] And / or, the thickness of the adhesive layer along the stacking direction of the encapsulation structure is 2μm~8μm.

[0019] In some possible implementations, the reinforcing fibers include carbon fibers and / or glass fibers.

[0020] And / or, the inner liner may also include a silane coupling agent.

[0021] And / or, the liner may also include thermoplastic polyurethane.

[0022] In some possible implementations, the carbon fiber content in the liner is 10wt% to 40wt%.

[0023] And / or, the mass percentage of glass fiber in the lining layer is 10wt% to 30wt%.

[0024] And / or, the mass percentage of thermoplastic polyurethane in the liner is 3wt% to 10wt%.

[0025] In some possible implementations, the inner liner layer comprises a first sublayer, a second sublayer, and a third sublayer stacked sequentially, with the first sublayer located between the second sublayer and the metal barrier layer. The first sublayer comprises polyetheretherketone (PEEK) and glass fiber. The second sublayer is composed of PEEK. The third sublayer comprises PEEK and carbon fiber.

[0026] In some possible implementations, the inner liner is a co-extruded layer.

[0027] And / or, the mass percentage of glass fiber in the first sublayer is 10wt% to 30wt%.

[0028] And / or, the mass percentage of carbon fiber in the third sublayer is 10wt% to 40wt%.

[0029] And / or, the third sublayer may also include a silane coupling agent.

[0030] And / or, the third sublayer also includes thermoplastic polyurethane, which accounts for 3 wt% to 10 wt% of the mass of the third sublayer.

[0031] Secondly, embodiments of this application provide a method for manufacturing any of the packaging structures provided in the first aspect, comprising:

[0032] Provide a metal barrier layer, and fabricate multiple interlocking holes on the metal barrier layer.

[0033] A liner composite layer is provided, and a portion of the liner composite layer is embedded in a fitting hole. The liner composite layer includes polyetheretherketone and is used to contact the solid-state battery cell.

[0034] Provide a protective layer that connects to the metal barrier layer.

[0035] In some possible implementations, creating multiple interlocking holes on the metal barrier layer includes: anodizing the metal barrier layer to form multiple interlocking holes on the metal barrier layer.

[0036] And / or, the inner liner composite layer includes an adhesive layer and an inner liner layer stacked together, the inner liner layer including polyetheretherketone, and embedding a portion of the inner liner composite layer into the interlocking holes includes: disposing the adhesive layer on the surface of a metal barrier layer having interlocking holes; melting the inner liner layer at a first temperature, extruding it into a film by co-extrusion, and cooling and curing it through multi-level gradient temperature control to obtain an inner liner film; and hot-pressing the inner liner film, the adhesive layer and the metal barrier layer together at a second temperature.

[0037] Thirdly, embodiments of this application provide a solid-state battery, including any of the packaging structures provided in the first aspect and a solid-state cell packaged inside the packaging structure.

[0038] The encapsulation structure, the method for manufacturing the encapsulation structure, and the solid-state battery provided in this application embodiment are all made of a material containing polyether ether ketone (PEEK). PEEK has excellent heat resistance and stability. In the high-temperature operating range of the solid-state battery and under hot-pressing encapsulation conditions, the molecular chain segments remain stable and will not soften, swell, or precipitate small molecule organic matter, thereby effectively avoiding contamination of the solid electrolyte interface.

[0039] Considering the thermal expansion coefficient mismatch between polyetheretherketone (PEEK) and the metal barrier layer, multiple spaced micro-interlocking holes are formed on the surface of the metal barrier layer facing the inner liner composite layer. Part of the inner liner composite layer embeds itself within these interlocking holes during the lamination process, constructing a dense micro-physical interlocking / anchoring network at the interface between the two. This significantly enhances the interfacial bonding force between the inner liner composite layer and the metal barrier layer, effectively eliminating the risk of interlayer delamination and peeling under long-term charge-discharge vibration, alternating thermal shock, and cell volume expansion stress. Attached Figure Description

[0040] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0041] Figure 1 This is a schematic diagram of a solid-state battery provided in an embodiment of this application;

[0042] Figure 2 This is a schematic diagram of a metal barrier layer provided in an embodiment of this application;

[0043] Figure 3 This is a schematic flowchart illustrating a method for fabricating a packaging structure provided in an embodiment of this application.

[0044] Explanation of reference numerals in the attached figures:

[0045] 10. Packaging structure; 20. Solid-state battery cell;

[0046] 100. Protective layer;

[0047] 200. Metal barrier layer; 210. Fitting hole;

[0048] 300, Inner lining composite layer; 310, Adhesive layer; 320, Inner lining layer; 321, First sub-layer; 322, Second sub-layer; 323, Third sub-layer.

[0049] To facilitate understanding of the embodiments of this application, the spline curves and arrows used in the reference numerals in the accompanying drawings are explained below: the components indicated by spline curves without arrows can be solid components, that is, components with solid structures; the components indicated by spline curves with arrows can be virtual components, that is, components without solid structures; in some cases, the components indicated by spline curves with arrows can also be assemblies with solid structures or virtual structures.

[0050] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation

[0051] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings.

[0052] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In the description of the embodiments of this application, it should be understood that the terms "center," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicating orientation or positional relationships (if present), are based on the orientation or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on the embodiments of this application. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element. Where there is no conflict, embodiments of this application and the various features thereof can be combined with each other, all of which are within the scope of protection of this application.

[0053] With the rapid development of the new energy industry, solid-state batteries have become an important development direction for next-generation power batteries due to their higher safety and energy density. Solid-state batteries also require sealing of the solid-state cells through encapsulation structures to isolate them from external moisture and oxygen corrosion of the internal materials. Therefore, the performance of the solid-state cell encapsulation structure directly affects the lifespan and safety of the all-solid-state battery.

[0054] Related technologies provide an aluminum-plastic film used as an encapsulation structure for battery cells. Specifically, the aluminum-plastic film includes a nylon layer, an aluminum foil layer, and a polypropylene layer stacked sequentially from the outside to the inside. The nylon layer is located on the outermost side, providing protection against external mechanical scratches and abrasion. The aluminum foil layer is located in the middle layer, preventing the penetration of moisture and oxygen. The polypropylene layer is located on the innermost side and is bonded to the polypropylene layer of another aluminum-plastic film by heat fusion bonding to form a sealed cavity, thereby achieving sealed encapsulation of the battery cell.

[0055] However, in some scenarios, such as high-temperature scenarios with temperatures greater than or equal to 80°C, or hot-press packaging scenarios, the polypropylene layer will soften, swell, and precipitate small molecule organic matter, which will then contaminate the solid electrolyte interface, leading to a reduction in the electrochemical performance and cycle life of the battery cell.

[0056] Figure 1 This is a schematic diagram of a solid-state battery provided in an embodiment of this application. Figure 2 This is a schematic diagram of a structure of the metal barrier layer 200 provided in an embodiment of this application.

[0057] In view of this, such as Figure 1 and Figure 2 As shown in the figure, this application embodiment provides a packaging structure 10 for packaging a solid-state battery cell 20, including a protective layer 100, a metal barrier layer 200, and an inner liner composite layer 300 stacked sequentially. The inner liner composite layer 300 comprises polyetheretherketone (PEEK) and is used to contact the solid-state battery cell 20. The metal barrier layer 200 has a plurality of spaced-apart fitting holes 210 on its side facing the inner liner composite layer 300, and a portion of the inner liner composite layer 300 is embedded within the fitting holes 210.

[0058] In the encapsulation structure 10 provided in this application embodiment, the inner liner composite layer 300 is made of a material containing polyetheretherketone (PEEK). PEEK has excellent heat resistance and stability, with a long-term tolerance temperature of 250°C to 260°C. During the high-temperature operating range of solid-state batteries and under hot-pressing encapsulation conditions, the molecular chain segments remain stable, preventing softening, swelling, and precipitation of small organic molecules, thus effectively avoiding contamination of the solid electrolyte interface. Simultaneously, PEEK possesses strong chemical inertness, enabling it to form a dense physical barrier for solid electrolytes, especially highly active sulfide solid electrolytes, preventing contact between the solid electrolyte and the metal barrier layer 200, thereby suppressing interlayer side reactions and electrochemical corrosion gas generation.

[0059] During the charging and discharging process of solid-state cell 20, its negative electrode undergoes significant volume expansion and contraction. Without continuous pressure restraint, this volume change can lead to poor solid-solid contact, increased interfacial impedance, and consequently, capacity decay, or even a sudden drop in capacity. Polyetheretherketone (PEEK) itself possesses high elastic modulus and excellent creep resistance, providing reliable rigid structural support and anti-expansion restraint for solid-state cell 20. Thus, under the harsh environment of long-term pressure and temperature cycling, the inner liner composite layer 300 hardly undergoes creep relaxation, thereby continuously maintaining a constant interfacial contact pressure inside solid-state cell 20, preventing interfacial detachment and a surge in electrochemical impedance, and significantly improving the cycle life of solid-state cell 20.

[0060] Polyetheretherketone (PEEK) material combines high dielectric insulation with extremely high mechanical puncture strength, effectively preventing microscopic punctures from electrode cutting burrs and lithium dendrites, thus eliminating the risk of micro-short circuits inside the battery cell. Furthermore, PEEK exhibits low-smoke flame retardancy and non-flowing properties under extreme high-temperature conditions, and does not produce liquid conductive melts when thermally damaged. This design significantly enhances the intrinsic safety of the solid-state battery cell 20 under thermal runaway extreme conditions.

[0061] Considering the mismatch in thermal expansion coefficients between polyetheretherketone (PEEK) and the metal barrier layer 200, multiple spaced micro-interlocking holes 210 are provided on the surface of the metal barrier layer 200 facing the inner liner composite layer 300. Part of the inner liner composite layer 300 embeds itself within these interlocking holes 210 during the lamination process, constructing a dense micro-physical interlocking / anchoring network at the interface between the two. This significantly enhances the interfacial bonding force between the inner liner composite layer 300 and the metal barrier layer 200, achieving an interlayer peel strength exceeding 15 MPa. This effectively eliminates the risk of interlayer peeling and delamination under long-term charge-discharge vibration, alternating thermal shock, and cell volume expansion stress.

[0062] The outer protective layer 100 can resist external mechanical scratches and environmental wear, while the middle metal barrier layer 200 can completely block the penetration and intrusion of external water vapor and oxygen.

[0063] In some embodiments, the embedding of a portion of the inner lining composite layer 300 into the interlocking hole 210 can be achieved through various processing methods such as hot pressing, melt casting coating, molding embossing, or solvothermal curing and infiltration. This allows the resin material of the inner lining composite layer 300, which is in a molten or plasticized state when heated, to fully rheologically fill the internal micro-cavities of the interlocking hole 210 under external pressure, thereby solidifying and bonding with the metal barrier layer 200 after cooling and shaping.

[0064] In some possible implementations, the fitting hole 210 is an anodized hole.

[0065] And / or, the depth of the fitting hole 210 along the stacking direction of the packaging structure 10 is 5μm~25μm.

[0066] And / or, the protective layer 100 is a nylon layer.

[0067] And / or, the metal barrier layer 200 is an aluminum foil layer.

[0068] And / or, the thickness of the protective layer 100 along the stacking direction of the encapsulation structure 10 is 15μm to 35μm.

[0069] And / or, the thickness of the metal barrier layer 200 along the stacking direction of the encapsulation structure 10 is 30μm~50μm.

[0070] The interlocking holes 210 are set as anodic oxidation holes, that is, the interlocking holes 210 generated by the anodic oxidation process have the characteristics of uniform pore size distribution, high porosity and strong bonding with the metal substrate, thereby providing a high-density micro-interlocking structure for the inner lining composite layer 300, which in turn significantly improves the interlayer bonding strength between the metal barrier layer 200 and the inner lining composite layer 300.

[0071] The depth of the interlocking hole 210 along the stacking direction is limited to the range of 5μm to 25μm. This not only ensures that the material of the inner lining composite layer 300 can fully penetrate into the pores to form a deep anchorage to achieve high peel resistance, but also effectively avoids the weakening of the effective solid thickness and water and oxygen barrier performance of the metal barrier layer 200 due to the interlocking hole 210 being too deep.

[0072] The protective layer 100 is made of nylon. By utilizing the excellent abrasion resistance and mechanical scratch resistance of nylon material, it can provide reliable external mechanical impact protection and weather protection for the outer surface of the encapsulation structure 10, effectively preventing damage to the outer layer.

[0073] The metal barrier layer 200 is made of aluminum foil. Aluminum foil is lightweight, has low processing cost, and excellent deep drawing ductility. In this way, it can not only form a dense barrier against external water vapor and oxygen, but also provide sufficient structural stiffness and compressive support for the overall packaging structure 10.

[0074] In addition, limiting the thickness of the protective layer 100 to 15μm~35μm ensures the external mechanical protection strength and puncture resistance while avoiding redundant weight increase of the outer layer, which is beneficial to improving the volumetric energy density of the battery cell.

[0075] The thickness of the metal barrier layer 200 is limited to 30μm~50μm, thereby effectively balancing the lightweight and deep-drawing formability of the packaging structure 10 while ensuring good water and oxygen barrier effect and packaging rigidity support.

[0076] In some embodiments, the interlocking hole 210 can be formed by processes such as chemical etching, micro-arc oxidation, laser drilling or plasma micro-etching, in addition to being anodized holes.

[0077] In some embodiments, the depth of the fitting hole 210 can be any point value or a range of values ​​consisting of any two points among 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm or 25μm.

[0078] In some embodiments, the cross-sectional shape of the interlocking hole 210 is not limited to a straight cylindrical hole, but can also be an inverted conical hole, a stepped hole, a flask-shaped hole, or an interconnected network of pores with lateral branches, as long as it can accommodate the infiltration of part of the material of the inner lining composite layer 300 and form a physical interlocking shape after curing.

[0079] In some embodiments, the protective layer 100 may be replaced with a polyethylene terephthalate (PET) layer, a polyethylene naphthalate (PEN) layer, a polyimide (PI) layer, or a nylon layer, in addition to a nylon layer.

[0080] In some embodiments, the thickness of the protective layer 100 can be any point value of 15μm, 18μm, 20μm, 25μm, 28μm, 30μm, 32μm or 35μm or a range of values ​​consisting of any two points therein.

[0081] In some embodiments, the metal barrier layer 200 may be replaced with stainless steel foil, copper foil, titanium foil, nickel foil, or a metal-plated polymer composite barrier film, in addition to aluminum foil, depending on the operating conditions.

[0082] In some embodiments, the thickness of the metal barrier layer 200 can be any point value or a range of values ​​consisting of any two points among 30μm, 32μm, 35μm, 38μm, 40μm, 42μm, 45μm, 48μm or 50μm.

[0083] In some embodiments, the metal barrier layer 200 may be a single-layer rolled metal foil or a functional metal sheet that has undergone surface passivation, micro-arc oxidation or micro-roughening pretreatment to meet the requirements of different corrosion resistance levels and mechanical support strength.

[0084] In some possible implementations, such as Figure 1As shown, the inner liner composite layer 300 includes an adhesive layer 310 and an inner liner layer 320 stacked together. The adhesive layer 310 is disposed between the metal barrier layer 200 and the inner liner layer 320, and at least a portion of the adhesive layer 310 is embedded in the interlocking hole 210. The inner liner layer 320 includes polyetheretherketone.

[0085] Alternatively, the inner liner composite layer 300 may include an inner liner layer 320, which may include polyetheretherketone (PEEK), with a portion of the inner liner layer 320 embedded within the interlocking hole 210.

[0086] When the inner liner composite layer 300 is laminated with the adhesive layer 310 and the inner liner layer 320, the adhesive layer 310 acts as a transition buffer medium between the metal barrier layer 200 and the inner liner layer 320. During the composite heating process, the adhesive layer 310 has good hot melt flowability, which can fully flow and densely fill the interlocking holes 210 embedded in the metal barrier layer 200, thereby significantly improving the microscopic chemical wetting performance and interfacial physical interlocking effect between the inner liner composite layer 300 and the metal surface. At the same time, the adhesive layer 310 can effectively absorb and release the thermal mismatch stress caused by the difference in thermal expansion coefficients between polyetheretherketone and the metal material. This configuration significantly reduces the concentration of interfacial shear stress, thereby greatly improving the peel bond strength between the metal barrier layer 200 and the inner liner layer 320.

[0087] When the inner liner composite layer 300 uses a single inner liner layer 320 and is directly embedded in the interlocking hole 210, the polyetheretherketone substrate is directly plastically deformed and anchored in the micropores during the hot pressing process. This eliminates the need for an intermediate adhesive medium, greatly simplifying the material layers and manufacturing process of the encapsulation structure 10, and reducing the physical contact interfaces between layers within the structure. This avoids potential hazards such as aging degradation and delamination failure of the adhesive under long-term electrochemical environments or under heat and pressure conditions, and also reduces raw material and manufacturing costs. Therefore, this solution balances structural simplicity, high interface reliability, and economy.

[0088] In some possible implementations, the liner 320 is composed of polyetheretherketone (PEEK), or the liner 320 comprises PEEK and reinforcing fibers.

[0089] And / or, the thickness of the inner liner 320 along the stacking direction of the encapsulation structure 10 is 30 μm to 80 μm.

[0090] And / or, adhesive layer 310 is a polyetherimide layer.

[0091] And / or, the thickness of the adhesive layer 310 along the stacking direction of the encapsulation structure 10 is 2μm to 8μm.

[0092] When the inner liner 320 is composed of polyetheretherketone, due to the high purity and good chemical stability of polyetheretherketone itself, impurities can be avoided from being introduced into the battery cell system, thereby giving the encapsulation structure 10 superior electrical insulation and avoiding the pollution of the interface by the precipitation of small molecule volatiles.

[0093] When the inner liner 320 includes polyetheretherketone and reinforcing fibers, the reinforcing fibers form a high-strength skeleton in the polyetheretherketone matrix, which significantly improves the tensile modulus, structural stiffness and puncture resistance of the inner liner 320. In this way, the creep resistance and pressure retention capability of the inner liner 320 under long-term pressure conditions are greatly improved.

[0094] When the thickness of the inner liner 320 along the stacking direction is limited to 30μm~80μm, it can provide sufficient dielectric barrier and mechanical support thickness to ensure reliable insulation and puncture resistance as well as constant voltage support rigidity. On the other hand, it can avoid the material becoming brittle due to excessive thickness, thus taking into account machinability and preventing the loss of cell volumetric energy density due to excessive thickness of the inner liner 320 occupying internal space.

[0095] When the adhesive layer 310 is a polyetherimide layer, since polyetherimide and polyetheretherketone have similar molecular structures and excellent compatibility, and polyetherimide has a temperature resistance greater than 260℃, it has excellent heat resistance and good hot melt flowability. After being heated, it can flow fully and penetrate deeply into the interlocking hole 210, thereby forming a high-temperature resistant and high-strength microscopic physical interlocking and molecular fusion bonding between the metal barrier layer 200 and the inner liner layer 320.

[0096] When the thickness of the adhesive layer 310 along the stacking direction is limited to 2μm~8μm, this thickness can ensure that the molten polyetherimide is evenly spread and tightly fills the interlocking holes 210, thereby achieving a strong interfacial bond. It can be seen that this avoids insufficient wetting and bonding defects caused by an excessively thin adhesive layer 310, and effectively prevents creep shear or delamination under high temperature stress when the adhesive layer 310 is too thick, thereby improving the overall heat resistance stability.

[0097] In some embodiments, the thickness of the inner liner 320 can be flexibly adjusted within the range of 30μm to 80μm to adapt to different cell capacity requirements. Specifically, the thickness of the inner liner 320 along the stacking direction can be 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, etc., or a thickness range consisting of any two of the above values.

[0098] In some embodiments, when the inner liner composite layer 300 adopts a double-layer structure, the adhesive layer 310 disposed between the metal barrier layer 200 and the inner liner layer 320 can be a polyetherimide layer. In some optional embodiments, the thickness of the polyetherimide adhesive layer 310 along the lamination direction can be specifically selected as 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, or 8μm, or any sub-interval within the range of 2μm to 8μm.

[0099] As an alternative, the adhesive layer 310 can be made of high-temperature resistant thermoplastic resin, such as polyetherimide, modified polyetheretherketone, or thermoplastic polyimide, or it can also be made of high-temperature resistant epoxy adhesive or silane-modified adhesive. The adhesive layer 310 can be formed by pre-film hot-pressing lamination, extrusion coating, or solution casting.

[0100] In some possible implementations, the reinforcing fibers include carbon fibers and / or glass fibers.

[0101] And / or, the inner liner 320 also includes a silane coupling agent.

[0102] And / or, the inner liner 320 also includes thermoplastic polyurethane.

[0103] Specifically, when the reinforcing fiber includes carbon fiber, the ultra-high modulus and excellent thermal conductivity of carbon fiber can significantly improve the high-temperature creep resistance and dimensional stability of the polyetheretherketone (PEEK) liner 320, thereby helping to quickly dissipate heat from the battery cell during charge-discharge cycles and maintain a constant interfacial surface pressure for a long time.

[0104] When the reinforcing fiber includes glass fiber, the glass fiber has both excellent electrical insulation and high mechanical strength, which can significantly enhance the structural stiffness and puncture resistance of the inner liner 320 while reliably ensuring the insulation safety of the encapsulation structure 10.

[0105] When the reinforcing fiber contains both carbon fiber and glass fiber, it can effectively combine the high modulus creep resistance of carbon fiber with the high dielectric insulation advantage of glass fiber, thereby achieving a synergistic improvement in mechanical support and electrical insulation performance.

[0106] In addition, by introducing a silane coupling agent into the inner liner 320, the interfacial wettability and compatibility between the reinforcing fiber and the polyether ether ketone matrix can be significantly improved. This can greatly increase the interfacial shear strength between the fiber and the resin matrix by about 40%, without significantly increasing the matrix hardness.

[0107] Meanwhile, the thermoplastic polyurethane added to the inner liner 320 has outstanding high elasticity and elongation toughness, which can effectively compensate for the increased material brittleness caused by the reinforcing fiber filling, thereby significantly improving the dynamic flexibility of the composite material and enabling it to withstand multiple bending and molding without cracking.

[0108] In some embodiments, in addition to being selected from one or a combination of two of carbon fiber and glass fiber, the reinforcing fiber may be replaced or supplemented with other high-temperature resistant and high-strength inorganic or organic reinforcing fillers such as aramid fiber, basalt fiber, silicon carbide whiskers, boron nitride nanotubes or alumina fiber, so as to adjust the thermal expansion coefficient, dielectric constant or mechanical stiffness of the inner liner 320 according to different battery cell environments.

[0109] In some embodiments, the silane coupling agent may be selected from silane compounds containing active groups such as amino, epoxy, methacryloxy, or mercapto groups, such as KH-550, KH-560, etc., depending on the functional group requirements of the reinforcing fibers and resins. Alternatively, it may be replaced with titanate coupling agents, aluminate coupling agents, or polymeric compatibilizers, such as grafted modified polyether ether ketone, to achieve similar effects in improving interfacial wetting and stress transfer.

[0110] In some embodiments, the thermoplastic polyurethane (TPU) can be selected from polyester-type TPU or polyether-type TPU according to the processing temperature and flexibility requirements, or it can be replaced with other thermoplastic elastomers or compatible resins with good temperature resistance and moderate elastic modulus, so as to achieve the purpose of toughening and preventing brittle cracking of the inner lining layer at 320 while ensuring heat resistance.

[0111] In some possible implementations, the carbon fiber accounts for 10 wt% to 40 wt% of the mass of the liner 320.

[0112] And / or, the mass percentage of glass fiber in the inner lining 320 is 10wt% to 30wt%.

[0113] And / or, the mass percentage of thermoplastic polyurethane in the inner liner 320 is 3wt% to 10wt%.

[0114] By limiting the mass percentage of carbon fiber in the inner liner 320 to 10wt%~40wt%, within this range, the carbon fiber can construct a continuous and dense microscopic mechanical reinforcement network in the polyetheretherketone matrix, thereby endowing the inner liner 320 with extremely high tensile strength, tear resistance, and resistance to burr penetration at the battery cell edge. This fully utilizes the mechanical reinforcement and creep resistance properties of carbon fiber while effectively avoiding the problems of increased composite brittleness and deteriorated melt flowability caused by excessive carbon fiber introduction.

[0115] The mass percentage of glass fiber in the inner liner 320 is limited to 10wt%~30wt%. Based on the high insulation resistance characteristics of glass fiber, under the appropriate mass percentage, the glass fiber is evenly dispersed in the matrix and is not prone to agglomeration. Thus, while ensuring that the inner liner 320 has excellent electrical insulation performance, the dimensional stability and high temperature creep resistance of the inner liner 320 are significantly improved, thereby maintaining the original ductility and toughness of the polyetheretherketone matrix.

[0116] The mass percentage of thermoplastic polyurethane in the inner liner 320 is limited to 3wt%~10wt%. Due to its excellent segmental flexibility and high elasticity, thermoplastic polyurethane can effectively buffer stress concentration caused by reinforcing fibers, thereby significantly improving the impact toughness of the inner liner composite material under normal and even low-temperature conditions. This setting also improves melt adhesion flow during subsequent heat sealing, greatly enhancing the melt-bonding density and sealing barrier reliability of the heat-sealed interface. Thus, because its addition amount is within a moderately low proportion range, it will not worsen the stringent control indicators for small molecule precipitation in the encapsulation material.

[0117] In some embodiments, the mass percentage of carbon fiber in the inner lining layer 320 can be specifically 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, or 40wt%, or it can be a range consisting of any two of the above values, such as 15wt%~35wt%, 20wt%~30wt%, etc.

[0118] In some embodiments, the mass percentage of glass fiber in the inner lining layer 320 can be specifically 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 25wt%, or 30wt%, etc., or it can be a range consisting of any two of the above values, such as 12wt%~28wt%, 15wt%~25wt%, etc.

[0119] In some embodiments, the mass percentage of thermoplastic polyurethane in the inner liner 320 can be specifically 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, or 10wt%, or it can be a range consisting of any two of the above values, such as 4wt%~8wt%, 5wt%~7wt%, etc.

[0120] In some possible implementations, such as Figure 1 As shown, the inner liner 320 includes a first sublayer 321, a second sublayer 322, and a third sublayer 323 stacked sequentially, with the first sublayer 321 located between the second sublayer 322 and the metal barrier layer 200. The first sublayer 321 comprises polyetheretherketone (PEEK) and glass fiber. The second sublayer 322 is composed of PEEK. The third sublayer 323 comprises PEEK and carbon fiber.

[0121] Glass fiber has an extremely low coefficient of thermal expansion. When it is combined with polyetheretherketone to form the first sublayer 321 and placed near the metal barrier layer 200, the overall coefficient of thermal expansion of the first sublayer 321 can be effectively brought closer to the metal barrier layer 200. This significantly reduces the concentration of interlayer shear thermal stress caused by thermal expansion and contraction mismatch when the encapsulation structure 10 is subjected to thermal cycling. As a result, the interfacial bonding strength between the inner liner layer 320 and the metal barrier layer 200 is greatly enhanced, preventing delamination.

[0122] Meanwhile, the second sublayer 322 is composed of pure polyether ether ketone and serves as an intermediate interlayer. Because it does not contain heterogeneous fillers such as fibers, it can form a dense and uniform resin matrix transition layer. This can block the microscopic interface leakage channels that may be formed by the reinforcing fibers in the first sublayer 321 and the third sublayer 323, thereby providing excellent heat-resistant electrical insulation performance and long-lasting chemical barrier continuity for the encapsulation structure 10.

[0123] In addition, the third sub-layer 323 includes polyetheretherketone and carbon fiber and is in direct contact with the solid cell 20. The carbon fiber has ultra-high tensile modulus and mechanical strength. This arrangement can build a high-strength wear-resistant and tear-resistant network on the surface of the solid cell 20, thereby effectively resisting the micro-puncture of the electrode edge burrs and mechanical friction loss during the charging and discharging expansion process of the solid cell 20.

[0124] In some embodiments, the glass fibers in the first sublayer 321 may be in the form of chopped fibers, fiber whiskers, or nanoglass microspheres.

[0125] In some embodiments, the carbon fibers in the third sublayer 323 may be in the form of chopped fibers, fiber whiskers, or nanoglass microspheres.

[0126] In some embodiments, the polyetheretherketone resin in the second sublayer 322 may be selected as low-viscosity, medium-viscosity, or high-viscosity polyetheretherketone according to the melt index requirement.

[0127] In some embodiments, the thicknesses of the first sublayer 321 and the third sublayer 323 may be symmetrically distributed, or the thickness of the first sublayer 321 near the metal barrier layer 200 may be greater than the thickness of the third sublayer 323, depending on specific performance requirements, so as to enhance the stress buffering effect.

[0128] In some possible implementations, the inner liner 320 is a co-extruded layer.

[0129] And / or, the mass percentage of glass fiber in the first sublayer 321 is 10wt% to 30wt%.

[0130] And / or, the carbon fiber accounts for 10wt% to 40wt% of the mass of the third sublayer 323.

[0131] And / or, the third sublayer 323 also includes a silane coupling agent.

[0132] And / or, the third sublayer 323 also includes thermoplastic polyurethane, the thermoplastic polyurethane accounting for 3wt% to 10wt% of the mass of the third sublayer 323.

[0133] When the inner liner 320 is a co-extruded layer, the first sub-layer 321, the second sub-layer 322 and the third sub-layer 323 achieve interpenetration and entanglement of molecular chain segments in a high-temperature molten state, achieving molecular-level interface fusion. This completely avoids the delamination and shedding of each sub-layer during subsequent molding, bending processing and long-term cyclic service, and significantly simplifies the multi-layer composite molding process of the inner liner 320.

[0134] When the mass percentage of glass fiber in the first sublayer 321 is 10wt%~30wt%, while maintaining excellent electrical insulation properties, the glass fiber effectively suppresses the thermal expansion and compressive creep of polyetheretherketone (PEEK), significantly improving the dimensional stability and creep resistance of the first sublayer 321. Simultaneously, due to the moderate filler concentration, agglomeration is not easily observed, and the toughness of the matrix PEEK is fully preserved. This results in a better compatibility between the thermomechanical properties of the first sublayer 321 and the metal barrier layer 200.

[0135] When the carbon fiber content in the third sublayer 323 is 10wt%~40wt%, the carbon fiber constructs a high-density rigid reinforcing network on the surface layer that directly contacts the battery cell. This endows the third sublayer 323 with extremely high tensile strength, tear resistance, and resistance to electrode burr penetration, while maintaining good microscopic smoothness of the surface. This content range fully utilizes the mechanical reinforcing effect of carbon fiber while effectively avoiding the problems of material embrittlement and deterioration of melt flowability caused by excessive carbon fiber addition.

[0136] When the third sublayer 323 also includes a silane coupling agent, the silane coupling agent, after hydrolysis and condensation, builds a chemical bond bridge between the carbon fiber surface and the polyether ether ketone resin molecular chain, which significantly improves the interfacial wettability and compatibility between the two, reduces microscopic defects and voids at the phase interface, thereby improving the efficiency of external stress transmission between the matrix and the reinforcing fiber.

[0137] When the third sublayer 323 also includes thermoplastic polyurethane with a mass ratio of 3wt% to 10wt%, the highly elastic polyurethane molecular chains are uniformly interspersed in the rigid network, so that the surface of the contact cell has both the ultra-high mechanical strength of carbon fiber and excellent hot melt adhesion and dynamic flexibility, which makes it easy to achieve a high-density, high-strength, and reliable heat seal at the edge of the cell during sealing.

[0138] In some embodiments, the co-extrusion method of the inner liner 320 can be multi-layer co-extrusion casting, and in other embodiments, it can be multi-layer co-extrusion blown film forming or multi-layer co-extrusion casting.

[0139] In some embodiments, fiber axial orientation can be achieved by ultrasonic-assisted extrusion, resulting in a longitudinal / transverse softness difference of <15%.

[0140] In some embodiments, the mass percentage of glass fiber in the first sublayer 321 may be specifically 10wt%, 15wt%, 20wt%, 25wt%, or 30wt%, or a range of values ​​formed by any two of the above points.

[0141] In some embodiments, the mass percentage of carbon fiber in the third sublayer 323 can be specifically 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, or 40wt%, or a numerical range formed by any two of the above points.

[0142] In some embodiments, the silane coupling agent may be selected from: aminosilane coupling agents, such as γ-aminopropyltriethoxysilane KH-550; epoxysilane coupling agents, such as γ-(2,3-epoxypropoxy)propyltrimethoxysilane KH-560; methacryloyloxysilane coupling agents, such as KH-570; and vinylsilane coupling agents. The silane coupling agent may be selected from one or more combinations of the above coupling agents.

[0143] In some embodiments, the thermoplastic polyurethane may be selected from at least one of polyester-type thermoplastic polyurethane, polyether-type thermoplastic polyurethane, or polycaprolactone-type thermoplastic polyurethane.

[0144] In some embodiments, the mass percentage of thermoplastic polyurethane in the third sublayer 323 may be specifically 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, or 10wt%, or a range of values ​​consisting of any two of the above points.

[0145] Figure 3 This is a schematic flowchart illustrating a method for fabricating the packaging structure 10 provided in an embodiment of this application.

[0146] like Figure 3 As shown, this application embodiment also provides a method for manufacturing any of the aforementioned packaging structures 10, including:

[0147] S100, a metal barrier layer 200 is provided, and a plurality of fitting holes 210 are formed on the metal barrier layer 200.

[0148] S200, an inner liner composite layer 300 is provided, and a portion of the inner liner composite layer 300 is embedded in the fitting hole 210. The inner liner composite layer 300 includes polyetheretherketone and is used to contact the solid-state battery cell 20.

[0149] S300, Provide a protective layer 100, and connect the protective layer 100 to the metal barrier layer 200.

[0150] First, multiple micro-interlocking holes 210 are pre-processed on the inner surface of the metal barrier layer 200 to provide a substrate interlocking structure for subsequent interlayer composite.

[0151] Furthermore, when the inner liner composite layer 300 containing polyetheretherketone (PEEK) is provided and bonded, a portion of the inner liner composite layer 300 material flows or is pressed into the interlocking hole 210, thereby constructing a dense microscopic physical interlocking / anchoring network in situ between the metal barrier layer 200 and the inner liner composite layer 300. This significantly improves the wetting and adhesion state between the polyetheretherketone material and the metal substrate, thereby greatly enhancing the interlayer peel bond strength and effectively suppressing subsequent delamination failure under long-term thermal cycling and charge-discharge stress.

[0152] Meanwhile, the inner lining composite layer 300 is used as the innermost working surface in contact with the solid cell 20. By utilizing the high heat resistance, high chemical inertness and high elastic modulus of polyether ether ketone, it can not only avoid the contamination of the solid electrolyte interface by small molecule precipitates, but also withstand the continuous surface pressure during the cycling process of the solid cell 20 without creep relaxation.

[0153] Finally, the protective layer 100 is compositely bonded to the outer surface of the metal barrier layer 200 on the side opposite to the inner liner composite layer 300, thereby providing a weather-resistant, scratch-resistant, and mechanically buffered barrier for the overall encapsulation structure 10.

[0154] It can be seen that the manufacturing method has a compact process connection and high process controllability. By using the physical anchoring mechanism of micropores and the intrinsic high performance of polyetheretherketone material, it achieves a synergistic improvement in the interlayer bonding force of the 10 layers of the encapsulation structure, the absence of exudation pollution and high creep resistance.

[0155] Specifically, the manufacturing method of the packaging structure 10 in this application adopts all the technical solutions of any of the aforementioned packaging structures 10, and therefore has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be repeated here.

[0156] In some possible implementations, forming a plurality of interlocking holes 210 on the metal barrier layer 200 includes: anodizing the metal barrier layer 200 to form a plurality of interlocking holes 210 on the metal barrier layer 200.

[0157] And / or, the inner liner composite layer 300 includes an adhesive layer 310 and an inner liner layer 320 stacked together, the inner liner layer 320 including polyetheretherketone, and embedding a portion of the inner liner composite layer 300 into the interlocking hole 210 includes: disposing the adhesive layer 310 on the surface of the metal barrier layer 200 having the interlocking hole 210; melting the inner liner layer 320 at a first temperature, extruding it into a film by co-extrusion, and cooling and curing it by multi-level gradient temperature control to obtain the inner liner layer 320 film; and hot-pressing the inner liner layer 320 film, the adhesive layer 310 and the metal barrier layer 200 together at a second temperature.

[0158] The metal barrier layer 200 is anodized, resulting in anodized pores on its surface that are highly uniform in pore size, have high micro-porosity, and are firmly bonded to the metal substrate. This provides a dense and stable micro-anchoring framework for the subsequent filling and infiltration of the lining material, thereby forming a strong physical interlock at the interface and effectively improving the interlayer bonding strength.

[0159] The inner liner 320 containing polyether ether ketone is melted at a first temperature and extruded into a film by co-extrusion, so that the polyether ether ketone substrate and each component can be uniformly dispersed and fully mixed under melt flow dynamics, thereby ensuring the thickness consistency and structural flatness of the obtained inner liner 320 film.

[0160] After extrusion and film formation, the film is further cooled and cured by multi-level gradient temperature control. This allows for precise control of the nucleus growth kinetics and grain size distribution of polyetheretherketone during the cooling and crystallization process. This effectively eliminates residual thermal stress and orientation stress inside the film, avoiding film warping, embrittlement, or microcrack defects caused by excessively rapid local cooling and uneven crystallization.

[0161] The adhesive layer 310 is pre-set on the surface of the metal barrier layer 200 with the interlocking hole 210. Then, the inner liner 320 film, the adhesive layer 310 and the metal barrier layer 200 are hot-pressed together at a second temperature, so that the adhesive layer 310 is fully softened and melted under heat and pressure and exhibits excellent wetting fluidity, thereby being able to wet and deeply fill the interlocking hole 210 formed by anodizing, while venting out trace amounts of residual gas at the bonding interface.

[0162] In some embodiments, the process of anodizing the metal barrier layer 200 to form the interlocking holes 210 can employ processes such as oxalic acid anodizing, sulfuric acid anodizing, phosphoric acid anodizing, or mixed acid anodizing. The anodizing process can be in constant voltage mode or constant current mode. In other alternative embodiments, the means of fabricating the interlocking holes 210 can also be replaced by surface roughening processes that can form microporous or pit arrays on the metal surface, such as micro-area chemical etching, laser micro-hole processing, plasma micro-etching, electrochemical micro-etching, or micro / nano roll imprinting.

[0163] In some embodiments, the first temperature for melt co-extrusion of the inner liner layer 320 can be 360°C to 420°C, which can be adjusted according to the melt processing window of the polyetheretherketone substrate and the formulation components such as reinforcing fibers that may be present. Co-extrusion molding can be completed using a multi-layer co-extrusion die or a single-layer co-extrusion casting equipment.

[0164] As an alternative, the inner liner 320 film can also be formed using plastic processing techniques such as solution casting, blow molding, calendering, or compression stretching.

[0165] In some embodiments, the multi-stage gradient temperature-controlled curing process may include two, three, four, or more stages of stepped temperature control and cooling. The cooling medium may employ multiple sets of temperature-controlled rollers or zoned temperature-controlled annealing tunnels, for example, sequentially passing through a high-temperature crystallization and setting temperature zone, an annealing stress-relief temperature zone, and a cooling and curing temperature zone to achieve gradient control of crystallinity and grain morphology. Specifically, the high-temperature crystallization and setting temperature zone is 250°C to 320°C, the annealing stress-relief temperature zone is 180°C to 240°C, and the cooling and curing temperature zone is room temperature to 150°C. In other embodiments, a programmed annealing device with continuously linear cooling rate control may also be used to achieve stress relief and slow curing.

[0166] In some embodiments, the adhesive layer 310 is disposed on the surface of the metal barrier layer 200 by means of microgravure coating, slot-die coating, doctor blade coating, or spraying, etc., to uniformly apply the adhesive solution to the metal barrier layer 200 and then dry it to form a film. The adhesive solution is, for example, a polar solvent solution of polyetherimide. In other embodiments, the adhesive layer 310 may also be a pre-formed adhesive film, which is pre-laid on the surface of the metal barrier layer 200 by low-temperature pre-bonding.

[0167] In some embodiments, the second temperature of hot pressing is typically higher than the glass transition temperature of the adhesive layer 310 and lower than the thermal decomposition temperature of the inner liner 320 material, for example, it can be set to 280°C to 360°C, and the hot pressing pressure can be set in the range of 0.5MPa to 10MPa. The laminating equipment can be a double-strand continuous hot press, a multi-pass hot roller press, or a flatbed hot press.

[0168] After hot pressing and lamination, cooling and shaping rollers can be used for pressure holding and cooling to ensure that the multi-layered composite structure has excellent flatness.

[0169] This application also provides a solid-state battery, including any of the aforementioned packaging structures 10 and a solid-state cell 20 packaged inside the packaging structure 10.

[0170] In some embodiments, the solid-state battery can be an all-solid-state battery, and the electrolyte can be a sulfide, oxide, polymer, composite electrolyte, etc.

[0171] In some embodiments, the solid-state battery may also be a semi-solid-state battery, and the electrolyte may be a polymer, gel, oxide, sulfide, composite electrolyte, etc.

[0172] In some embodiments, the solid-state battery is a 10Ah all-solid-state battery, and the basic design information of the 10Ah all-solid-state battery is as follows:

[0173] A positive electrode formulation: NMC811:Li6PS5Cl:VGCF:PTFE=83:13:3:1.

[0174] A negative electrode formulation: Si:SEBS:VGCF=94:2.5:3.5.

[0175] The electrolyte is a polymer + sulfide composite electrolyte.

[0176] The battery cell dimensions are 280mm*110mm*12mm.

[0177] Specifically, the solid-state battery in this application adopts all the technical solutions of any of the aforementioned packaging structures 10, and therefore has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be repeated here.

[0178] This application also provides an electrical device, including a device body and a solid-state battery connected to the device body.

[0179] Among them, electrical equipment can be vehicles, household appliances, digital products, toys, industrial equipment, aerospace equipment, etc.

[0180] Specifically, the electrical equipment in this application adopts all the technical solutions of the aforementioned solid-state battery, and therefore has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be repeated here.

[0181] The following are two specific embodiments and a comparative embodiment provided in this application:

[0182] Comparative Example 1:

[0183] During encapsulation, an aluminum-plastic film is used, with an outer nylon layer of 25μm thickness. The middle layer is an aluminum foil layer of 40μm thickness. The inner layer is a polypropylene layer of 50μm thickness.

[0184] Example 1:

[0185] During encapsulation, the protective layer 100 is a nylon layer with a thickness of 25 μm. The metal barrier layer 200 is an aluminum foil layer with a thickness of 40 μm. The inner liner composite layer 300 includes an inner liner layer 320 and an adhesive layer 310. The inner liner layer 320 is composed of polyetheretherketone material with a thickness of 50 μm; the adhesive layer 310 is a polyetherimide layer with a thickness of 5 μm.

[0186] Example 2:

[0187] During encapsulation, the protective layer 100 is a nylon layer with a thickness of 25 μm. The metal barrier layer 200 is an aluminum foil layer with a thickness of 40 μm. The inner liner composite layer 300 includes an inner liner layer 320 and an adhesive layer 310. The adhesive layer 310 is a polyetherimide layer with a thickness of 5 μm; the inner liner layer 320 has a thickness of 40 μm. The inner liner layer 320 includes a first sublayer 321, a second sublayer 322, and a third sublayer 323 stacked sequentially. The first sublayer 321 is located between the second sublayer 322 and the metal barrier layer 200. The first sublayer 321 includes polyetheretherketone (PEEK) and glass fiber, with the glass fiber accounting for 20 wt% of the first sublayer 321. The second sublayer 322 is composed of PEEK. The third sublayer 323 includes PEEK and carbon fiber, with the carbon fiber accounting for 30 wt% of the third sublayer 323. The third sublayer 323 also includes a silane coupling agent, such as KH550. The third sublayer 323 also includes thermoplastic polyurethane, which accounts for 6 wt% of the mass of the inner liner 320.

[0188] Test conditions: At 35℃, after two cycles of activation at 0.1C, the device is cyclically operated at a current of 1C within a voltage range of 2.5V to 4.2V, with a test pressure of 6MPa. The test pressure is the pressure applied by the fixture.

[0189] Finally, the results of the cell capacity retention rate are shown in Table 1:

[0190] Table 1 - Comparison of Cell Capacity Retention Rate Results

[0191]

[0192] It should be understood that the embodiments of this application are not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of this application is limited only by the appended claims.

Claims

1. A packaging structure for packaging solid-state battery cells, characterized in that, It includes a protective layer, a metal barrier layer, and an inner lining composite layer that are stacked in sequence; The inner liner composite layer comprises polyetheretherketone (PEEK) and is used to contact the solid-state battery cell. The metal barrier layer has a plurality of spaced-apart fitting holes on the side facing the inner lining composite layer, and a portion of the inner lining composite layer is embedded in the fitting holes.

2. The packaging structure according to claim 1, characterized in that, The fitting hole is an anodized hole; And / or, the depth of the fitting hole along the stacking direction of the packaging structure is 5μm~25μm; And / or, the protective layer is a nylon layer; And / or, the metal barrier layer is an aluminum foil layer; And / or, the thickness of the protective layer along the stacking direction of the encapsulation structure is 15μm~35μm; And / or, the thickness of the metal barrier layer along the stacking direction of the packaging structure is 30μm~50μm.

3. The packaging structure according to claim 1 or 2, characterized in that, The inner liner composite layer includes an adhesive layer and an inner liner layer stacked together. The adhesive layer is disposed between the metal barrier layer and the inner liner layer, and at least a portion of the adhesive layer is embedded in the interlocking hole. The inner liner layer includes polyetheretherketone. Alternatively, the inner liner composite layer may include an inner liner layer comprising polyetheretherketone, with a portion of the inner liner layer embedded within the interlocking holes.

4. The packaging structure according to claim 3, characterized in that, The inner liner is composed of polyetheretherketone (PEEK), or the inner liner comprises PEEK and reinforcing fibers. And / or, the thickness of the inner liner layer along the stacking direction of the encapsulation structure is 30μm~80μm; And / or, the adhesive layer is a polyetherimide layer; And / or, the thickness of the adhesive layer along the stacking direction of the encapsulation structure is 2μm~8μm.

5. The packaging structure according to claim 4, characterized in that, The reinforcing fibers include carbon fibers and / or glass fibers; And / or, the inner liner layer further includes a silane coupling agent; And / or, the inner liner also includes thermoplastic polyurethane.

6. The packaging structure according to claim 5, characterized in that, The carbon fiber in the inner lining layer accounts for 10wt% to 40wt% by mass. And / or, the glass fiber accounts for 10wt% to 30wt% of the mass percentage in the lining layer; And / or, the thermoplastic polyurethane accounts for 3wt% to 10wt% of the mass of the liner.

7. The packaging structure according to claim 3, characterized in that, The inner liner includes a first sub-layer, a second sub-layer, and a third sub-layer stacked sequentially, with the first sub-layer located between the second sub-layer and the metal barrier layer; The first sublayer comprises polyetheretherketone and glass fiber; The second sublayer is composed of polyetheretherketone; The third sublayer comprises polyetheretherketone and carbon fiber.

8. The packaging structure according to claim 7, characterized in that, The inner liner is a co-extruded layer; And / or, the glass fiber accounts for 10wt% to 30wt% of the mass percentage in the first sublayer; And / or, the carbon fiber accounts for 10wt% to 40wt% of the mass percentage in the third sublayer; And / or, the third sublayer further includes a silane coupling agent; And / or, the third sublayer further includes thermoplastic polyurethane, wherein the thermoplastic polyurethane accounts for 3wt% to 10wt% of the mass of the third sublayer.

9. A method for manufacturing a packaging structure as described in any one of claims 1-8, characterized in that, include: A metal barrier layer is provided, and a plurality of interlocking holes are formed on the metal barrier layer; A liner composite layer is provided, and a portion of the liner composite layer is embedded in the fitting hole. The liner composite layer comprises polyetheretherketone and is used to contact the solid-state battery cell. A protective layer is provided, which is then connected to the metal barrier layer.

10. The method for manufacturing the packaging structure according to claim 9, characterized in that, The step of forming multiple interlocking holes on the metal barrier layer includes: performing anodizing treatment on the metal barrier layer to form multiple interlocking holes on the metal barrier layer; And / or, the inner liner composite layer includes an adhesive layer and an inner liner layer stacked together, the inner liner layer including polyetheretherketone, and the step of embedding a portion of the inner liner composite layer into the interlocking hole includes: disposing the adhesive layer on the surface of the metal barrier layer having the interlocking hole; melting the inner liner layer at a first temperature, extruding it into a film by co-extrusion, and cooling and curing it through multi-level gradient temperature control to obtain an inner liner film; and hot-pressing the inner liner film, the adhesive layer and the metal barrier layer together at a second temperature.

11. A solid-state battery, characterized in that, It includes the packaging structure as described in any one of claims 1-8 and the solid-state battery cell packaged inside the packaging structure.